Implementasi Fiqh Muamalah Dalam Hukum Ekonomi Syariah Pada Transaksi Modern - Nala Amalia; Mohd Winario; Rahmawati Rahmawati; Yudi Irwan (Journal of Economic, Management, Business, Accounting Sustainability, 2026)
This study aims to analyze the implementation of Islamic jurisprudence (fiqh muamalah) within Islamic economic law in modern transactions and to examine the relevance of Islamic principles to the development of the contemporary economic system. Technological developments and the digitalization of the economy have given rise to various forms of modern transactions, such as e-commerce, fintech, digital wallets, and online investments, which require Islamic legal studies to ensure their compliance with Islamic principles. This study employed a qualitative research method with a library research approach. Data were obtained from the Quran, hadith, books, scientific journals, fatwas from the National Council of Islamic Scholars (DSN-MUI), and various other literature related to Islamic jurisprudence (fiqh muamalah) and Islamic economic law. Data analysis was conducted using a descriptive-analytical technique, examining the concepts, principles, and implementation of Islamic jurisprudence (fiqh muamalah) in modern transactions. The results show that Islamic jurisprudence (fiqh muamalah) has the flexibility to address modern economic developments as long as the transactions do not contain elements of usury (riba), gharar (gharar), maysir (gambling), and harmful practices. The implementation of Islamic principles in modern transactions can create a more just, transparent, and socially beneficial economic system.